Fatigue in levodopa-naive subjects with Parkinson disease - Schifitto, G; Friedman, J H; Oakes, D; Shulman, L; Comella, C L; Marek, K; Fahn, S (Neurology, 2008)
Fatigue is a common complaint in Parkinson disease (PD). We investigated fatigue in a cohort of previously untreated patients with early PD enrolled in the Earlier vs Later Levodopa (ELLDOPA) clinical trial. A total of 361 patients were enrolled in the randomized, double-blind, placebo-controlled ELLDOPA trial and assigned to receive placebo or carbidopa-levodopa 37.5/150 mg, 75/300 mg, or 150/600 mg daily for 40 weeks, followed by a 2-week medication washout period. Subjects who scored >4 on the Fatigue Severity Scale were classified as fatigued. PD severity was assessed using the Unified Parkinson's Disease Rating Scale (UPDRS), Hoehn-Yahr scale, and Schwab-England Activities of Daily Living Scale. A subgroup of subjects underwent [(123)I]-beta-CIT SPECT to measure striatal dopamine transporter density. Of the 349 ELLDOPA subjects who completed fatigue measures, 128 were classified as fatigued at baseline. The fatigued group was significantly more impaired neurologically (UPDRS, all subscales and Hoehn and Yahr staging) and functionally (Schwab-England Scale) but no significant differences were observed in beta-CIT measurements between the two groups. Analysis of covariance showed a greater increase in fatigue score from baseline to the end of the 2-week washout in the placebo group (0.75 points) than in the three groups receiving levodopa (increases of 0.30 [150 mg/day], 0.36 [300 mg/day], and 0.33 [600 mg/day]; p = 0.03 for heterogeneity). Fatigue is a frequent symptom in early, untreated, non-depressed patients with Parkinson disease (PD), affecting over 1/3 of the patients in this cohort at baseline and 50% by week 42. Fatigue was associated with the severity of PD, and progressed less in patients treated with levodopa.